Assessing the Nationwide Impact of a Registry-Based Randomized Clinical Trial on Cardiovascular Practice: The TASTE Trial in Perspective. (March 2019) - Buccheri, Sergio; Sarno, Giovanna; Fröbert, Ole; Gudnason, Thorarinn; Lagerqvist, Bo; Lindholm, Daniel; Maeng, Michael; Olivecrona, Göran; James, Stefan
Abstract : Background: Registry-based randomized clinical trials have emerged as useful tools to provide evidence on the comparative efficacy and safety of different therapeutic strategies. However, it remains unknown whether the results of registry-based randomized clinical trials have a sizable impact on daily clinical practice. We sought, therefore, to describe the temporal trends in thrombus aspiration (TA) use in Sweden before, during, and after dissemination of the TASTE trial (Thrombus Aspiration in ST-Elevation Myocardial Infarction in Scandinavia) results. Methods and Results: From January 1, 2006, to December 31, 2017, we included all consecutive patients with ST-segment–elevation myocardial infarction undergoing percutaneous revascularization in Sweden. All patients were registered in the Swedish Coronary Angiography and Angioplasty Registry. A total of 55 809 ST-segment–elevation myocardial infarction patients were included. TA use in Sweden substantially decreased after dissemination of TASTE results (from 39.8% to 11.8% during and after TASTE, respectively). Substantial variability in TA use across treating centers was observed before TASTE (TA use ranging from 0% to 70%), but after TASTE both the interhospital variability and the frequency of TA use were markedly reduced. A constant shift in medical practice was seen about 4 months after dissemination of the TASTE trial results. Time trends for all-cause mortality and definite stent thrombosis at 30 days were not associated with variations in TA use ( P values >0.05 using the Granger test). Conclusions: In Sweden, the results of the TASTE trial were impactful in daily clinical practice and led to a relevant decrease in TA use in ST-segment–elevation myocardial infarction patients undergoing percutaneous revascularization. Abstract : Supplemental Digital Content is available in the text.